2014
DOI: 10.5194/cp-10-405-2014
|View full text |Cite
|
Sign up to set email alerts
|

Persistent millennial-scale link between Greenland climate and northern Pacific Oxygen Minimum Zone under interglacial conditions

Abstract: Abstract. The intensity and/or extent of the northeastern Pacific Oxygen Minimum Zone (OMZ) varied in-phase with the Northern Hemisphere high latitude climate on millennial timescales during the last glacial period, indicating the occurrence of atmospheric and oceanic connections under glacial conditions. While millennial variability was reported for both the Greenland and the northern Atlantic Ocean during the last interglacial period, the climatic connections with the northeastern Pacific OMZ has not yet bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 100 publications
(153 reference statements)
4
23
0
Order By: Relevance
“…High-amplitude variability (such as the one described in our results) is superimposed over the long-term millennial-multimillenial O 2 trends (Nameroff et al, 2004;Cartapanis et al, 2014;Chang et al, 2014;Moffitt et al, 2015;Praetorius et al, 2015;Tetard et al, 2017). In contrast, the long-term tendencies (e.g., transition from the Last Glacial Maximum toward the Holocene) are driven by global changes in temperature and circulation that control intermediate and deep-water oxygenation (Ganeshram and Pedersen, 1998;Hendy and Pedersen, 2006;Cartapanis et al, 2014;Praetorius et al, 2015;Lu et al, 2016;Choumiline et al, 2017;Breitburg et al, 2018;Levin, 2018). In other words, short-term decreases in anoxia during warm times in response to the weakening of the Walker Circulation and increase abundance of ENSO years can counteract long-term warming of the upper ocean, which causes stratification and reduced ventilation and O 2 concentration on the global scale ocean.…”
Section: Drivers Of Redox In the Eastern Pacific And Apparent Contradsupporting
confidence: 58%
See 2 more Smart Citations
“…High-amplitude variability (such as the one described in our results) is superimposed over the long-term millennial-multimillenial O 2 trends (Nameroff et al, 2004;Cartapanis et al, 2014;Chang et al, 2014;Moffitt et al, 2015;Praetorius et al, 2015;Tetard et al, 2017). In contrast, the long-term tendencies (e.g., transition from the Last Glacial Maximum toward the Holocene) are driven by global changes in temperature and circulation that control intermediate and deep-water oxygenation (Ganeshram and Pedersen, 1998;Hendy and Pedersen, 2006;Cartapanis et al, 2014;Praetorius et al, 2015;Lu et al, 2016;Choumiline et al, 2017;Breitburg et al, 2018;Levin, 2018). In other words, short-term decreases in anoxia during warm times in response to the weakening of the Walker Circulation and increase abundance of ENSO years can counteract long-term warming of the upper ocean, which causes stratification and reduced ventilation and O 2 concentration on the global scale ocean.…”
Section: Drivers Of Redox In the Eastern Pacific And Apparent Contradsupporting
confidence: 58%
“…A clear distinction should be made between the dominant mechanisms that control oxygenation in the ETNP over decadalcentennial timescales (Deutsch et al, 2014;Tems et al, 2015Tems et al, , 2016 and those that govern long-term glacial-interglacial variability (Ganeshram and Pedersen, 1998;Nameroff et al, 2004;Hendy and Pedersen, 2006;Ivanochko et al, 2008;Pichevin et al, 2012Pichevin et al, , 2014Cartapanis et al, 2014;Umling and Thunell, 2017). High-amplitude variability (such as the one described in our results) is superimposed over the long-term millennial-multimillenial O 2 trends (Nameroff et al, 2004;Cartapanis et al, 2014;Chang et al, 2014;Moffitt et al, 2015;Praetorius et al, 2015;Tetard et al, 2017).…”
Section: Drivers Of Redox In the Eastern Pacific And Apparent Contradmentioning
confidence: 75%
See 1 more Smart Citation
“…In Lake El'gygytgyn sediments Sr is mainly associated with the occurrence of Na-Ca-feldspars and K-feldspars from the surrounding acidic and andesitic volcanic rocks (Wennrich et al, 2013) substituting for sodium, calcium, or potassium (El Bouseily and El Sokkary, 1975;Cherniak and Watson, 1994). Due to its similar ionic radius, Rb, in contrast, preferentially replaces K (Chang et al, 2013), and thus is commonly found in K-feldspars as well as mica and clay minerals (Kylander et al, 2011;Fralick and Kronberg, 1997). Hence, Rb is typically enriched in the fine-grained sediment fraction of weathering products of silicates (Koenig et al, 2011;Dypvik and Harris, 2001).…”
Section: Rb and Srmentioning
confidence: 99%
“…The Rb / Sr (or Sr / Rb) ratio is commonly used as an indicator of the weathering intensity of the bedrock in different kinds of sediments records (e.g., Chang et al, 2013;Jin et al, 2001;Dasch, 1969;Heymann et al, 2013), but has also been interpreted in terms of grain-size variations of Siberian lakes Teletskoye and El'gene-Kyuele (Kalugin et al, 2007;Biskaborn et al, 2013). Previous studies of Lake El'gygytgyn sediments on interglacial/glacial timescales attributed variations in the Rb / Sr ratio mainly to an enhanced Sr depletion due to higher chemical alteration, which in turn is controlled by grain size (Minyuk et al, 2011(Minyuk et al, , 2014.…”
Section: Rb and Srmentioning
confidence: 99%